2018
DOI: 10.1136/tobaccocontrol-2018-054599
|View full text |Cite
|
Sign up to set email alerts
|

Assessing progress in protecting non-smokers from secondhand smoke

Abstract: Scotland has witnessed a dramatic reduction in SHS exposure in the past two decades, but there are still nearly one in five non-smoking adults who have measurable exposure to SHS on any given day. Tobacco control strategies globally should consider the use of both the proportion of non-smoking adults with undetectable salivary cotinine and the GM as targets to encourage policies that achieve a smoke-free future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…However, a decrease in the concentration of salivary cotinine from tobacco, as an objective index of second-hand smoke exposure, was reported in children aged 11-12 years in Scotland after the 2006 legislation, 4 and non-smoking adults were around 6 times less likely to have had detectable second-hand smoke exposure in 2016 than in 1998. 21 The same might be assumed for children after TiRO. Thirdly, our analyses showed decreases in hospital admissions for asthma (and some other conditions related to second-hand smoke exposure) after the 2006 smoke-free public spaces legis lation, and in some subgroups after TiRO in 2014, but admissions for gastroenteritis (a condition unrelated to second-hand smoke exposure) were unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…However, a decrease in the concentration of salivary cotinine from tobacco, as an objective index of second-hand smoke exposure, was reported in children aged 11-12 years in Scotland after the 2006 legislation, 4 and non-smoking adults were around 6 times less likely to have had detectable second-hand smoke exposure in 2016 than in 1998. 21 The same might be assumed for children after TiRO. Thirdly, our analyses showed decreases in hospital admissions for asthma (and some other conditions related to second-hand smoke exposure) after the 2006 smoke-free public spaces legis lation, and in some subgroups after TiRO in 2014, but admissions for gastroenteritis (a condition unrelated to second-hand smoke exposure) were unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…These include measures such as smoke-free public spaces which have been shown to be highly effective in reducing both the proportion of non-smoking adults exposed to SHS and the intensity of that exposure. Recent work [53] examining population salivary cotinine data in Scotland has shown that the proportion of adult non-smokers with measurable cotinine on any given day has reduced from nearly 88% in 1998 to less than 19% in 2016; and the concentration of cotinine in the saliva of the non-smoking population has reduced by over 97%. Policy measures to reduce general smoking prevalence through tools such as taxation, pricing, and plain packaging; smoke-free legislation to reduce the number of enclosed public spaces where non-smokers are exposed to SHS; and mass media campaigns to reduce the acceptability of smoking at home, have all played a role in these reductions.…”
Section: Discussionmentioning
confidence: 99%
“…The longer than intended implementation of policy actions and the time for change to occur in smoking prevalence may explain why change in smoking prevalence was not observed until 2017, four years after the publication of the strategy. Additionally, the number of non-smokers exposed to second-hand smoke has decreased [8]. Further monitoring and evaluation is necessary to understand longer-term impacts of policy actions, and whether observed changes in prevalence of cigarette smoking is sustained.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the 2013 tobacco control strategy evaluated the impact of policy actions to reduce tobacco consumption, and highlighted promise for policies aimed at reducing children’s exposure to second-hand smoke, the implementation of a tobacco display ban in retail outlets, a mass media campaign ‘Take it Right Outside’, smoke-free hospital grounds, and the introduction of plain packaging legislation [6]. This review complements evaluations of tobacco control actions in Scotland and the UK which have identified promising effects (as well as challenges) for policies tackling second-hand smoke exposure [7,8], the implementation of a peer-led smoking prevention intervention in schools [9,10], mass media campaigns [11], tobacco packaging legislation [12], and point-of-sale legislation [13,14]. Globally, systematic review evidence has identified promising effects for tobacco control policies and interventions on reducing cigarette smoking prevalence and reducing inequalities in cigarette smoking [15,16,17,18,19], and observational research provides evidence for the implementation of multiple policy actions to reduce smoking prevalence [20].…”
Section: Introductionmentioning
confidence: 99%